Analisis Pemahaman Nilai Gotong-Royong dan Penerapannya dalam Sehari-Hari pada Pembelajaran PKN Kelas V di SD IT Al Munawwar - Halimah, Nur; Hanida, Rahmi Seri; Yusron, Ali (Lembaga Yasin AlSys, 2025)
The declining spirit of cooperation among elementary school students, as a consequence of modernization and individualism, underscores the urgency of revitalizing gotong royong values within educational settings. This study aims to analyze students’ understanding of gotong royong, describe its implementation in Civics Education (PKn) instruction, and identify supporting and inhibiting factors influencing its application at SD IT Al-Munawwar. A descriptive qualitative approach was employed, involving fifth-grade teachers and students selected through purposive sampling. Data collection methods included observation, interviews, and documentation, analyzed using the interactive model developed by Miles and Huberman, which encompasses data reduction, data display, and conclusion drawing/verification. The findings indicate that fifth-grade students possess a strong conceptual and practical understanding of gotong royong, demonstrated through classroom duties, group assignments, and concern for peers in need. This value is reinforced by teacher role models, participatory teaching methods, and a school culture that emphasizes togetherness. Inhibiting factors were minimal and predominantly observed among lower-grade students who require further guidance. The study concludes that gotong royong plays a vital role in shaping students’ social and moral character. The implications point to the need for strengthening character education theory grounded in Pancasila values and developing contextual learning models that foster cooperation, solidarity, and empathy at the elementary level.